UJl HASIL KEPRASAN BEBERAPA VARlETAS TEBU LAHAN KERING PADA DAERAH BERIKLIM BASAH - , Purwono; Sugeng Sudiatso; Dwi Guntoro (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
The study of first rationed sugar cane on wet climate region was carried out at Sindangbarang Bogor (belong to type A according Schmidt and Fergusson classification) from October 1993 to April 1994. The study was designed to fined out the yield and total-sugar content. Several cultivar of Ps 87 (produced by P3GI) were tested (Ps 87-985, Ps 87-21718, Ps 87-22189, Ps 87-22704, Ps 87-21781, Ps 87-22098, Ps 87-21781, Ps 87-21067), and Ps 58 as a control. The result showed that the Ps 87-22074 produced the highest yield (19.524,7 g/m